2020
DOI: 10.1002/ardp.202000079
|View full text |Cite
|
Sign up to set email alerts
|

5‐(4‐Methoxybenzylidene)thiazolidine‐2,4‐dione‐derived VEGFR‐2 inhibitors: Design, synthesis, molecular docking, and anticancer evaluations

Abstract: A novel series of 5‐(4‐methoxybenzylidene)thiazolidine‐2,4‐dione derivatives, 5a–g and 7a–f, was designed, synthesized, and evaluated for their anticancer activity against HepG2, HCT116, and MCF‐7 cells. HepG2 and HCT116 were the most sensitive cell lines to the influence of the new derivatives. In particular, compounds 7f, 7e, 7d, and 7c were found to be the most potent derivatives of all the tested compounds against the HepG2, HCT116, and MCF‐7 cancer cell lines. Compound 7f (IC50 = 6.19 ± 0.5, 5.47 ± 0.3, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…N ‐Substituted‐4‐phenylphthalazin‐1‐amine derivatives have the essential pharmacophoric features of VEGFR‐2 inhibitors [ 22,39‐44 ] (Figure 1), which include the following: First, there exists a six‐membered heteroaromatic ring, phthalazine, as a central aryl moiety, substituted with phenyl ring, as a hydrophobic portion, forming the 4‐phenylphthalazine scaffold. Second, the target phenyl group at position‐4 is used to replace pyridine and N ‐methylpicolinamide moieties of vatalanib and sorafenib (Figures 2 and 3), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…N ‐Substituted‐4‐phenylphthalazin‐1‐amine derivatives have the essential pharmacophoric features of VEGFR‐2 inhibitors [ 22,39‐44 ] (Figure 1), which include the following: First, there exists a six‐membered heteroaromatic ring, phthalazine, as a central aryl moiety, substituted with phenyl ring, as a hydrophobic portion, forming the 4‐phenylphthalazine scaffold. Second, the target phenyl group at position‐4 is used to replace pyridine and N ‐methylpicolinamide moieties of vatalanib and sorafenib (Figures 2 and 3), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of our efforts to obtain new anticancer agents, [ 37‐43 ] the goal of the present work was the synthesis of new agents with the same essential pharmacophoric features of the reported and clinically used VEGFR‐2 inhibitors (e.g., vatalanib and sorafenib). The main core of our molecular design rationale comprised bioisosteric modification strategies of VEGFR‐2 inhibitors at the four different pharmacophoric positions (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[ 21,22 ] Sorafenib (Nexavar®; IV ; (Figure 1) also is a potent VEGFR‐2 inhibitor and has been approved as an anti‐angiogenic drug. [ 23–25 ] Our reported compounds V [ 19 ] and VI [ 20 ] encourage us to synthesize new derivatives with the hydrophobic electron‐withdrawing mono‐, chloro‐, and/or dichlorobenzylidene instead of unsubstituted ( V ) or the hydrophobic electron‐donating methoxybenzylidenes ( VI ), respectively, to study the effect of these modifications on the activity.…”
Section: Introductionmentioning
confidence: 99%
“…A study reported by Shah et al, [12] showed that TZD derivative ciglitazone (I) ( Figure 1) significantly decreased the VEGF production in human granulose cells in an in vitro model. Extensive studies were reported in the synthesis of several 5-benzylidenethiazolidine-2,4-dione derivatives as potent anticancer agents [13][14][15][16][17][18][19][20] and potent VEGFR-2 inhibitors, for example, compound II. [2,12] Owing to the importance of VEGFR-2 in angiogenesis, this receptor is the most vital target in anti-angiogenic therapy against cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Recently, different small molecules have been designed as VEGFR inhibitors and anticancer agents. [20][21][22][23][24][25][26][27][28] The indolin-2-one analogs have been identified as effective angiogenesis inhibitors and multitargeted tyrosine kinases inhibitors. Sunitinib (SU11248) is the first small molecule possessing the indolin-2-one template against a variety of kinases such as VEGF receptor (VEGFR) types 1 (FLT1), 2 (KDR), and 3 (FLT4); the stem cell factor receptor (c-Kit); platelet-derived growth factor receptors A and B (PDGFRA and PDGFRB); colony-stimulating factor 1 receptor (CSF-1R); FMS-like tyrosine kinase 3 (FLT3); and glial cell line-derived neurotrophic factor receptor (RET), which received FDA approval and was marketed for the treatment of gastrointestinal stromal tumor (GIST) and renal cell carcinoma (RCC) in January 2006, and for pancreatic neuroendocrine tumors in May 2011.…”
mentioning
confidence: 99%